The prognostic value of the p53 gene expression and mutation in ovarian cancer (Medical Journal of Indonesia, 2009)
Aim This study aimed to observe the role of the p53 gene in ovarian carcinogenesis, and identify the prognostic significance of the expression of the p53 protein expression in ovarian cancer. Methods Fourty one ovarian cancer patients were examined in this study by analyzing the mutations of p53 gene from their blood samples, and by analyzing the p53 protein expression from ovarian cancer tissues. Results Mutational analysis in "hot spot" exons (exons 5-9) and in "non hot spot exon" (exon 11) was performed by PCR-sequencing methods and p53 expression analysis was performed by immunohistochemistry method. Mutations of p53 were found in all samples, and the mutations were mostly found in âhot spotâ exons, though few mutations were also found in "non hot spot" exon. The expression levels of p53 protein were found higher in advanced stages of ovarian cancer. Six month to two year post surgery follow-up of patients showed that high expression of p53 protein was in line with high mortality rate. Conclusion This study showed that the p53 gene could be used as a prognostic indicator of ovarian cancer. (Med J Indones 2009; 18:81-90). Keywords: p53, ovarian cancer, prognostic significance